Regulation of Recombination between gtfB/gtfC Genes in Streptococcus mutans by Recombinase A - Satoko Inagaki; Kazuyo Fujita; Yukiko Takashima; Kayoko Nagayama; Arifah C. Ardin; Yuki Matsumi; Michiyo Matsumoto-Nakano (The Scientific World Journal)
Streptococcus mutans produces 3 types of glucosyltransferases (GTFs), whose cooperative action is essential for cellular adhesion. The recombinase A (RecA) protein is required for homologous recombination. In our previous study, we isolated several strains with a smooth colony morphology and low GTF activity, characteristics speculated to be derived from the GTF fusions. The purpose of the present study was to investigate the mechanism of those fusions. S. mutans strain MT8148 was grown in the presence of recombinant RecA (rRecA) protein, after which smooth colonies were isolated. The biological functions and sequences of the gtfB and gtfC genes of this as well as other clinical strains were determined. The sucrose-dependent adherence rates of those strains were reduced as compared to that of MT8148. Determination of the sequences of the gtfB and gtfC genes showed that an approximately 3500 bp region was deleted from the area between them. Furthermore, expression of the recA gene was elevated in those strains as compared to MT8148. These results suggest that RecA has an important role in fusions of gtfB and gtfC genes, leading to alteration of colony morphology and reduction in sucrose-dependent adhesion.